2008
DOI: 10.3748/wjg.14.1399
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability and its association with the patient and disease characteristics in Crohn’s disease

Abstract: INTRODUCTIONIntestinal permeability (IP) is the property of the intestinal epithelium which refers to the facility with which it allows molecules to pass through by non-mediated diffusion [1] . IP has been implicated in the pathogenesis and frequent relapses of Crohn's disease (CD) [2][3][4][5][6] . Seven to 18% higher relapse rate has been reported in patients with increased IP compared to those with normal IP [7][8][9][10][11] . Moreover, RAPID COMMUNICATIONIntestinal permeability and its association with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 33 publications
3
49
0
2
Order By: Relevance
“…3,7,[36][37][38] Since AIEC bacteria are able to colonize colonic mucosa of mice expressing human CEACAMs molecules, we hypothesized that one of the consequences of AIEC/CEACAM6 interaction in CD patients could be the induction of claudin-2 expression, leading to increased intestinal permeability preceding inflammation in predisposed patients abnormally expressing CEACAM6. 9,39,40 Two independent studies reported in vitro that AIEC decreased the transepithelial resistance of the intestinal epithelial cell (IEC) monolayer and induced disorganization of F-actin and mislocalization of ZO-1 and E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,[36][37][38] Since AIEC bacteria are able to colonize colonic mucosa of mice expressing human CEACAMs molecules, we hypothesized that one of the consequences of AIEC/CEACAM6 interaction in CD patients could be the induction of claudin-2 expression, leading to increased intestinal permeability preceding inflammation in predisposed patients abnormally expressing CEACAM6. 9,39,40 Two independent studies reported in vitro that AIEC decreased the transepithelial resistance of the intestinal epithelial cell (IEC) monolayer and induced disorganization of F-actin and mislocalization of ZO-1 and E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…8 More recently, intestinal permeability was reported to be significantly increased in 36% of CD patients. 9 Vogelsang 10 recently suggested that environmental factors must be involved since 1) intestinal permeability can decrease over time even without ongoing therapy, 2) permeability is not increased in every patient with CD, and 3) permeability can be increased in spouses of CD patients. In parallel, bacterial translocation of E. coli, Enterococcus spp., Clostridium perfringens has been observed in the mesenteric nodes in 30%-50% of CD patients versus 5%-15% in healthy controls.…”
mentioning
confidence: 99%
“…specific distribution pattern of the tight junction proteins claudin 2, 3, 4, 5 and 8 in IBD patients. [69][70][71] Intestinal permeability is significantly increased in 36% of CD patients 72 and bacterial translocation of E. coli, Enterococcus spp., Clostridium perfringens has been observed in mesenteric nodes in 30-50% of CD patients versus 5-15% in healthy controls. 73,74 This could be due to: (1) bacterial uptake via Peyer's patches and (2) bacterial translocation due to abnormal tight junctions.…”
Section: Listeria Monocytogenes Bacteroides Vulgatus Bacteroides Burgmentioning
confidence: 99%
“…En nuestro paciente, la presencia de fiebre y hemocultivos positivos a E. coli tuvo una relación temporal y no necesariamente causal con el trasplante fecal. Los antecedentes de seis episodios de bacteriemia por E. coli y los dos presentados post-TMF pueden estar en el contexto de los trastornos de permeabilidad intestinal que presentan los pacientes con enfermedad de Crohn 29,30 . Recientemente estudios han demostrado el riesgo de reactivación de la colitis ulcerosa post TMF 26,28,31 poniendo en duda el rol del TMF en pacientes con EII 32 .…”
Section: Discussionunclassified